Use of alternative care sites during the COVID-19 pandemic in the city of Buenos Aires, Argentina. (May 2021) - Ferrante, Daniel; Macchia, Alejandro; González Villa Monte, Gabriel Alejo; Battistella, Gabriel; Baum, Analia; Zingoni, Paula; Angeleri, Patricia; Biscayart, Cristián; Walton, Carolina; Marcó, Florencia Flax; Esteban, Santiago; Mariani, Javier; et al.
Abstract: Objectives: In large cities, where a large proportion of the population live in poverty and overcrowding, orders to stay home to comply with isolation requirements are difficult to fulfil. In this article, the use of alternative care sites (ACSs) for the isolation of patients with confirmed COVID-19 or persons under investigation (PUI) in the City of Buenos Aires during the first wave of COVID-19 are described. Study design: This is a cross-sectional study. Methods: All patients with COVID-19 and PUI with insufficient housing resources who could not comply with orders to stay home and who were considered at low clinical risk in the initial triage were referred to refurbished hotels in the City of Buenos Aires (Ciudad Autónoma de Buenos Aires [CABA]). ACSs were divided into those for confirmed COVID-19 patients and those for PUI. Results: From March to August 2020, there were 58, 143 reported cases of COVID-19 (13, 829 of whom lived in slums) in the CABA. For COVID-19 positive cases, 62.1% (n = 8587) of those living in slums and 21.4% (n = 9498) of those living outside the slums were housed in an ACS. In total, 31.1% (n = 18, 085) of confirmed COVID-19 cases were housed in ACSs. In addition, 7728 PUI were housed (3178 from the slums) in an ACS. The average length of stay was 9.0 ± 2.5 days for patients with COVID-19 and 1.6 ± 0.7 days for PUI. For the individuals who were housed in an ACS, 1314 (5.1%) had to be hospitalised, 56 were in critical care units (0.22%) and there were 27 deaths (0.1%), none during their stay in an ACS. Conclusions: Overall, about one-third of all people with COVID-19 were referred to an ACS in the CABA. For slum dwellers, the proportion was >60%. The need for hospitalisation was low and severe clinical events were rare. This strategy reduced the pressure on hospitals so their efforts could be directed to patients with moderate-to-severe disease.